2010
DOI: 10.15208/pieb.2010.18
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of job satisfaction: A study of telecom sector

Abstract: This study is based on the assumption that "a happy worker is a productive worker". The research was conducted to identify the significance of those factors that lead towards job satisfaction and commitment of employees working in the telecom sector of Pakistan. The associations among pay and benefits, performance appraisal system, career development and management, supervision and collegiality and open communication (independent variables) were investigated with job satisfaction (dependent variable). The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The latest research (Riaz & Ramay, 2010;Baruch-Feldman et al, 2002) confirms these theses and indicates that satisfied employees are more devoted to job and more productive. The degree of correlation between job satisfaction and employees' productivity is 0.758 (Riaz & Ramay, 2010).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The latest research (Riaz & Ramay, 2010;Baruch-Feldman et al, 2002) confirms these theses and indicates that satisfied employees are more devoted to job and more productive. The degree of correlation between job satisfaction and employees' productivity is 0.758 (Riaz & Ramay, 2010).…”
Section: Introductionmentioning
confidence: 86%
“…The major issue with job satisfaction, identified by the authors (Aristovnik & Jaklič, 2013;Riaz & Ramay, 2010;Kim, 2002;Bernhardt et al, 2000), is imprecise definition of indicators that determine job satisfaction. This is particularly evident in the Western Balkans, where very few studies tackled this issue, and almost no studies dealt with job satisfaction in the retail sector.…”
Section: Introductionmentioning
confidence: 99%
“…al (2012). According to Riaz & Ramay (2010) job satisfaction is the employee's positive attitude towards a job and performance appraisal leads to career development which ultimately leads to job satisfaction. Similarly Yasminet (2012) concluded that HR systems impact the organization's performance and one of the key factors for the growth of telecom sector.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Human resources are valuable in the organizations; however, recently, organizational failure was linked with human resources. Telecommunication companies thrive to counter human resources related problems such as high attrition rates, expensive talent acquisition and management program in the telecom sector, customer dissatisfaction and switching [55,56], access management and connectivity [57], human resources productivity turn-over [58], wastage of time and other resources to loss of effective and efficient employee [58,59] and failure to imbibe the culture of a "happy worker is a productive worker" [60,61].…”
Section: Background Of the Studymentioning
confidence: 99%